Pengelolaan Fraktur Dentoalveolar pada Anak-Anak dengan Cap Splint Akrilik - Dedy Sigit Nur Cahyo; Maria Gorreti Widyastuti; Poerwati Soetji Rahajoe (Faculty of Dentistry, Universitas Gadjah Mada, 2015)
Management of Dentoalveolar Fractures in Children Using Acrylic Cap Splint. The purpose of fracture treatment in children is basically the same as that in adults with different management, while the choice of treatment method mainly relies on the development of jaws and teeth. It reports two cases of dentoalveolar fractures in children under 5 years old who were treated using acrylic cap splint with circum-mandibular wiring under general anesthetic. Two children, aged 1 year and 3 years old were referred to the emergency department of Dr. Sardjito Hospital with the diagnosis of dentoalveolar fractures. Both cases were treated using cap splint with circum-mandibular wiring-based fixation under general anesthetic. After 3 weeks, the acrylic cap splint and the circum-mandibular wiring were released under sedation. No loose teeth were found in the fracture area. In the following 6 weeks, the teeth were stable with normal occlusion and no infection found. Acrylic cap splint with circum-mandibular wiring is a simple, effective and minimally invasive method for dentoalveolar treatment in children.